Engaging European society at the forefront of cancer research and care: How discussions at the 5th Gago Conference on European Science policy led to the Heidelberg Manifesto - Baumann, Michael; Celis, Julio; Ringborg, Ulrik; Heitor, Manuel; Berns, Anton; Albreht, Tit; Arabadjiev, Jeliazko; Boutros, Michael; Brandenburg, Mario; Canhao, Helena; Carneiro, Fatima; Chomienne, Christine; et al. (Molecular oncology, 2023)
European cancer research stakeholders met in October 2022 in Heidelberg, Germany, at the 5th Gago conference on European Cancer Policy, to discuss the current cancer research and cancer care policy landscape in Europe. Meeting participants highlighted gaps in the existing European programmes focusing on cancer research, including Europe's Beating Cancer Plan (EBCP), the Mission on Cancer (MoC), Understanding Cancer (UNCAN.eu), and the joint action CRANE, and put forward the next priorities, in the form of the Heidelberg Manifesto for cancer research. This meeting report presents all discussions that shed light on how infrastructures can be effectively shaped for translational, prevention, clinical and outcomes cancer research, with a focus on implementation and sustainability and while engaging patients and the public. In addition, we summarize recommendations on how to introduce frameworks for the digitalization of European cancer research. Finally, we discuss what structures, commitment, and resources are needed to establish a collaborative cancer research environment in Europe to achieve the scale required for innovation.
Das th nach der Ziffer 5 wird im Titelzusatz hochgestellt
Online veröffentlicht: 20. März 2023
Gesehen am 22.05.2024